2001
DOI: 10.1017/s1366728901000116
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinguistic influence in bilingual language acquisition: Italian and French as recipient languages

Abstract: In this paper we want to compare the results from monolingual children with object omissions in bilingual children who have acquired two languages simultaneously. Our longitudinal studies of bilingual Dutch±French, German±French, and German±Italian children show that the bilingual children behave like monolingual children regarding the type of object omissions in the Romance languages. They differ from monolingual children with respect to the extent to which object drop is used. At the same time, the children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
474
5
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 421 publications
(539 citation statements)
references
References 73 publications
28
474
5
11
Order By: Relevance
“…Kupisch and Meisel remind us that, since the 1980s, a vast and important body of research has been conducted on child bilingualism and bilingual first language acquisition in Europe (De Houwer 2009, Deuchar and Quay 2000, Döpke 1992, Ezeizabarrena Segurola 2001, Lanza 2004, Meisel 1994, 2007, Müller and Hulk 2001, and, we would like to add, in Canada (Genesee 1989, Genesee et al 1995. This work has shown that young children keep their two linguistic systems separate from the onset of bilingual acquisition and go through the same developmental milestones in each language that monolingual children do.…”
Section: Heritage Speakers As Child Bilingualsmentioning
confidence: 99%
“…Kupisch and Meisel remind us that, since the 1980s, a vast and important body of research has been conducted on child bilingualism and bilingual first language acquisition in Europe (De Houwer 2009, Deuchar and Quay 2000, Döpke 1992, Ezeizabarrena Segurola 2001, Lanza 2004, Meisel 1994, 2007, Müller and Hulk 2001, and, we would like to add, in Canada (Genesee 1989, Genesee et al 1995. This work has shown that young children keep their two linguistic systems separate from the onset of bilingual acquisition and go through the same developmental milestones in each language that monolingual children do.…”
Section: Heritage Speakers As Child Bilingualsmentioning
confidence: 99%
“…The emerging grammars develop in a very similar way to the development of the corresponding monolingual L1 grammars. Hulk and Müller (2000) and Müller and Hulk (2001), among many others, have argued that cross-linguistic influence is nevertheless possible in certain vulnerable domains and in particular in the interface domain between syntax and pragmatics.…”
Section: Introductionmentioning
confidence: 99%
“…Sorace (1999Sorace ( , 2000a claims that interpretable features (in Chomsky's 1995 terms) are subject to language attrition and to residual optionality in L2 acquisition, whereas non-interpretable features are immune to attrition and don't exhibit residual optionality. Support for this distinction has recently begun to emerge from other areas of language development, such as bilingual first language acquisition (Müller and Hulk, 2001) and specific language impairment (Jakubowicz, 2000;Hamann et al, 1998). Further research is needed to explore-both theoretically and experimentally-these patterns of convergences, and more generally the modes of interaction of different constraints types in natural languages.…”
mentioning
confidence: 99%